A STUDY ON FLEECE CHARACTERIZATION OF HAMADANI SHEEP IN ERBIL PLAIN - Kasim O.Aziz (Mesopotamia Journal of Agriculture)
This study was undertaken on 196 Hamadani sheep (179 ewes & 17 rams) to characterize the fleece quantitatively and qualitatively and to determine the effect of flock ( 1 – 4 ), ewe age (1.5 to ≥ 5.5 years) and ewe status (barren, rearing single and twin lambs) on the studied traits besides the relationships among these traits. The results indicated that the overall means were: body weight 59.4 kg, greasy fleece weight 2.3 kg, staple length 11.9 cm, fiber length 18.3 cm, fiber diameter 37.2 μm, crimps 0.65 crimps/cm, medullated fibers 3.4 %, hairy fibers 59.4 %, fine fibers 36.7 %, heterotype fibers 1.1 % and kemp fibers 2.8 %. Furthermore, it was noticed that the grease content in greasy and scoured wool were 1.73 and 0.86 % respectively. Statistical analysis revealed a significant effect of flock on body weight, greasy fleece weight, staple length, fiber length, fiber diameter, crimps, medullated fibers, heterotype fibers and kemp fibers whereas, age of ewe affected only greasy fleece weight, staple length, fiber length and fiber diameter significantly.Non of the studied traits were affected significantly by ewe status.